Composition of The Essential Oils of Tanacetum densum (Lab.) Schultz Bip. subsp amani and T. densum (Lab.) Schultz Bip. subsp laxum (Asteraceae) from Turkey - Bagci, Eyup (Asian Journal of Chemistry, 2009)
The aerial parts of Tanacetum densum subsp. amani and T densum subsp. laxum were hydrodistilled to produce the oils with yields of 0.30% (v/w) and 0.15% v/w), respectively. The oils were analyzed by GC and GC/MS. Seventy three and seventy components were identified representing 92.2 and 80.6% of the oils, respectively. The main compounds of T densum subsp. amani were (x-pinene (3.0%),1,8-cineole (14.7%), borneol (31.3%) and endoborneol (21.0%). Whereas alpha-pinene (5.0%), (+)-epi-bicyclosesquiphellandrene (31.4%), alpha-cadinol (7.0%), 1-heptadecanol (5.6%) and eicosane (3.2%) were the major constituents in T densum subsp. laxum. Distribution of the predominate compounds in essential oil were discussed among the Tanacetum genus patterns.
Keywords: Tanacetum; Tanacetum densum; Essential oil; Borneol; 1,8-Cineole